Effectiveness of Roblox-Based Metaverse Learning Media in Enhancing Digital Literacy among Primary School Students in Technology-Limited Areas - Agustinus Sembiring; Handri Santoso; Heni Jusuf (CV. Media Inti Teknologi, 2026)
Background: The development of metaverse technology has opened up new opportunities in education, particularly through interactive platforms such as Roblox. However, most previous research has focused on schools with adequate technological access, leaving a gap in the implementation of the metaverse in areas with limited technology.Aims: This study examines the effectiveness of Roblox-based metaverse learning media in enhancing digital literacy among primary school students in technology-limited regions, contributing to inclusive digital learning strategies.Methods: The study employed a mixed-method approach with a quasi-experimental pretest–posttest design involving 118 students. A quantitative instrument in the form of a Likert-scale questionnaire was used to measure digital literacy, while qualitative data were obtained through open-ended interviews and documentation. The analysis was conducted using a paired sample t-test along with thematic analysis to enrich the interpretation of the results.Results: Quantitative findings show a significant improvement in digital literacy scores (t = -2.144; p = 0.034), with all five dimensions scoring above 3—especially Educational Game Evaluation (Mean = 3.464) and Attitudes and Perceptions (Mean = 3.451). Qualitative results reveal enthusiasm, engagement, and improved understanding of digital content. However, limited devices and unstable internet may reduce the consistency of students’ engagement.Conclusion: This study demonstrates that Roblox, as a metaverse-based learning medium, can be effectively adapted in elementary schools with limited technology. These findings underscore the importance of developing more adaptive learning media, providing clear instructions, and implementing educational policies that support equitable access to technology.